2010
DOI: 10.1186/1471-2180-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Pseudomonas aeruginosa lung infection in mice by recombinant OprF-pulsed dendritic cell immunization

Abstract: BackgroundThe Pseudomonas aeruginosa major constitutive outer membrane porin protein F (OprF) has been shown to be a protective antigen and was previously used to activate an immunological response in a mouse model of lung pneumonia. The purpose of our study was to demonstrate the ability of mouse dendritic cells pulsed with purified or recombinant OprF to protect mice against P. aeruginosa infection and inflammation.Both native (n-OprF), isolated and purified from PAO1 bacterial strain, and recombinant (histi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…The mouse model of P. aeruginosa lung infection was adapted from previously published protocols (37). Bacteria were grown at room temperature up to an OD 600 of 0.5 and were then collected by centrifugation, washed once in PBS, and resuspended again in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse model of P. aeruginosa lung infection was adapted from previously published protocols (37). Bacteria were grown at room temperature up to an OD 600 of 0.5 and were then collected by centrifugation, washed once in PBS, and resuspended again in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the phenotype of condensin mutations appeared rather mild, their effect on epigenetic states was quite dramatic. To determine whether or not these changes alter the virulence of P. aeruginosa, we evaluated ⌬smc and ⌬smc ⌬mksB strains in a mouse model of lung infection (37).…”
Section: Smc and Mksb Are Expendable And Antagonistic To Each Othermentioning
confidence: 99%
“…Intratracheal instillation is the most used method in HAP research and involves injecting the bacterial suspension directly into the trachea or lungs followed by air for dispersion of the bolus (33,(43)(44)(45)(46)(47)(48)(49)(50). This method gives the most precise control on the delivered dose.…”
Section: Types Of Pneumonia Modelsmentioning
confidence: 99%
“…OprF has intrinsic ability to stimulate release of diverse innate cytokines from dendritic cells (43); although this clearly would not have contributed to the differences in epitope focus we observed in peptide-specific CD4 responses, it may be that in chronically PA-infected patients showing up-regulated OprF, this upregulation may stimulate increased systemic IL-12 and tumor necrosis factor-a. From our study we cannot be certain whether the altered T-cell response pattern we observed is cause or effect of a heightened susceptibility to PA infection.…”
Section: Original Article Discussionmentioning
confidence: 63%